Exposure of tomato (Lycopersicon esculentum) to silver nanoparticles and silver nitrate: physiological and molecular response. Issue 1 (2nd January 2020) - Noori, Azam; Donnelly, Trevor; Colbert, Joseph; Cai, Wenjun; Newman, Lee A.; White, Jason C.
Abstract: Silver nanoparticles (AgNPs) are among the most widely used nanomaterials, with applications in sectors as diverse as communications, energy, medicine, and agriculture. This diverse application of AgNPs increases the risk of the release of these materials into the environment and raises the potential for transfer into plants and, subsequently, the human body. To better understand the effects of NPs in agricultural systems, this study investigates plant physiological and molecular responses upon exposure to AgNPs in comparison to silver nitrate (AgNO3 ). Tomato seedlings ( Lycopersison esculentum ) were exposed to 10, 20, or 30 mg/L silver (Ag), AgNO3, or AgNPs in hydroponic media for 7 days. A number of endpoints were measured, including plant growth, photosynthetic pigments, oxidative and antioxidant responses. The results showed 2–7 times lower growth rate in plants exposed to silver compared to the control. H2 O2 and malondialdehyde as oxidative stress indicators were, respectively, 1.7 and 4 times higher in plants exposed to all forms of silver compared to the control. The antioxidative responses increased significantly in plants exposed to Ag and AgNPs compared to the control. However, plants exposed to AgNO3 showed up to 50% lower enzymatic antioxidant activity. At the molecular level, the expression of genes involved in defense responses, including ethylene-inducing xylanase (EIX), peroxidase 51 (POX), and phenylalanine ammonia lyase, were significantly upregulated upon exposure to silver. The molecular and physiological data showed exposure to all forms of silver resulted in oxidative stress and exposure to AgNPs induced antioxidative and defense responses. However, exposure to AgNO3 resulted in phytotoxicity and failure in antioxidative responses. It indicates the higher reactivity and phytotoxicity of the ionic form of silver compared to NPs. The findings of this study add important information to efforts in attempting to characterize the exposure and risk associated with the release of nanomaterials in the environment.